Gestión administrativa del gobierno autónomo descentralizado del cantón Baba - Becilla Carpio, Jessenia Leonor (2020)
Administrative management is directly related to the administrative process, that is; with planning, organization, direction and control. The study has allowed us to determine how citizens value the municipal administration, an important part is the criteria of the inhabitants of the Baba canton, who are the ones who qualify the municipal administration, due to the fact that it is directed to satisfy their needs as a community. The support of the research is the legal provisions of the Organic Code of Territorial Organization, autonomy and decentralization -COOTAD- which directs the management of the GADs, the same that must be framed in the specific provisions, because the law in the public sector is for fulfill them, but not to interpret it. The document also describes the problems at the discretion of citizens that affect the smooth running of the municipal administration, considering this criterion based on the works being carried out, when there is work for a sector, administrative management is good, case On the contrary, they consider it negative or bad.